Issues Related to Diaspora Libraries and Reading in the Periodicals of Lithuanian Émigrés in the USA (till 1904) - Misiūnas, Remigijus (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English]A library is a multifaceted phenomenon. This multifacetedness is revealed in the definition of a library, it being a private or public book collection, or an educational institution, the mission of which is to collect, compile and store books as well as provide public access to them. Often, under the influence of historic circumstances, a more significant manifestation of certain aspects of its activity can be observed. This also applies to the role of libraries within the Lithuanian diaspora up to 1904. This article aims at analysing the situation prevailing in the Lithuanian diasporic libraries at that time and the efforts undertaken by the emigrees to compile printed periodicals in the libraries of foreign-born (non-Lithuanian) people. The aim was set to explore the attitude of the Lithuanian emigrants on the role of libraries, analyse the processes of setting up libraries and their activities as well as the efforts to compile Lithuanian periodicals in the foreigners’ libraries. Given the lack of research diaspora libraries, the article was prepared mainly on the basis of material collected from the periodicals issued at that time and available to the Lithuanian diaspora.Based on the collected material, it can be said that the idea of diaspora libraries is often related to the importance of education, self-education and reading, and often refers to the experiences of other nations and US public libraries. A small number of intellectuals among emigrants has resulted in few personal libraries being established and predetermined a seemingly slow emergence and development of emigrant libraries despite the encouragement to set them up. About a hundred libraries are believed to have been established or intended to be established. It was mainly the intellectuals or more educated emigrants who contributed to the process of developing libraries. They were founded by certain associations created specifically for this purpose or by other institutions such as various societies, clubs, etc., mainly concentrated in the numerous communities of Lithuanians living in Pennsylvania, Michigan, Connecticut, and severalso-called East Coast states of the United States. It is a fairly impressive figure, considering the conditions under which they were created and developed.Even though the archival function of libraries was understood and plans were made to create a library, the stock of which would cover the entire Lithuanian literature and the literature written by non-Lithuanians, such a library remained in an embryonic stage. The activities of the emigrants’ libraries were more focused on the model of a public library, taking into account the conditions of the time, first of all financial ones. These factors influenced the organizational structures (in particular, the creation of associations for the establishment and maintenance of special libraries), the fees to be paid for using library services by non-members of various associations and libraries, maintenance and development of libraries and the scope of library stock. The working hours and access to press periodicals depended on the availability of the persons responsible for the libraries, as they worked on a voluntary basis. Thus, in some libraries, books could be taken home, whereas in other libraries reading was only allowed on site, within the premises of a library, which served as a reading room as well. The funds for libraries’ maintenance were raised from the membership fees and library fees, the profit obtained from library-related events and other activities, not characteristic of libraries (for example, commercial press). Attempts were made to compensate shortage of funds by directy addressing publishers and asking them to donate their publications to library stock. However, such an attempt had an adverse effect on the development of publishing. Although funds had a significant impact on compiling collections, some libraries tried to follow a predetermined policy, for example, that of collecting and compiling all the press of the time or a certain part of it, compiling only secular literature or refusing to collect antireligious literature, etc.In the end of the 19 – beginning of the 20th century, the educational function of the library was highlighted, with library seen as a place where illiterate persons could learn to read, and those having basic education could further develop their skills. However, this activity, as well as the establishment of libraries in general, was influenced by the ideological differentiation that was prevailing within the Lithuanian diaspora at that time and different attitudes among emigrants towards library tasks. These factors and a low level of education among the emigrants account for a short existence of the majority of these libraries and scanty usage of library services.These factors had a negative effect on the attempts to supply the US public libraries with Lithuanian press periodicals. Despite the policies implemented by the then US public libraries and their attention to immigrants from eastern and southern Europe, some libraries, witnessing the lack of interest among Lithuanian emigrants in using library services, they refused to compile the Lithuanian press in their library stock. Furthermore, sometimes Lithuanians themselves did not show proper interest to promote Lithuanian periodicals.Still, considering the situation in the Lithuanian diaspora of those days, the prevailing level of literacy and culture among its members, it must be recognized that around a hundred libraries which were found or planned to be established during the period of a decade and a half is a considerable number, reflecting the efforts undertaken by a relatively small group of enthusiasts. The emergence of libraries and their activities influenced the mindset and attitudes of emigrants. In the course of time, libraries became a common phenomenon in Lithuanian communities, contributing to the development and strengthening of education and Lithuanian publishing in the United States.
Keywords: libraries, Lithuanian diaspora, publishing activities, reading